(untitled) (Research, Society and Development, 2021)
Brazilian environmental legislation is a strategic element for the achievement of sustainable development, in view of being the main command and control instrument that the State has to regulate productive and economic activities in general, by establishing the limits and norms in the relationship public-private. In this sense, the work aimed to analyze the main Brazilian environmental laws, pointing out their interface with the Sustainable Development Goals, proposed by the United Nations, and their goals. It is expected to contribute to future work in this area, given the joviality of the theme, in addition to enabling a more objective look at the subject, using as parameters the Sustainable Development Goals that will serve as a basis to identify those who come closest to the issues to contribute to the achievement of sustainable development.